2016
DOI: 10.18235/0000333
|View full text |Cite
|
Sign up to set email alerts
|

Crime and Violence in Jamaica: IDB Series on Crime and Violence in the Caribbean

Abstract: work is licensed under a Creative Commons IGO 3.0 AttributionNonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/ legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…[23, 27, 63] The way in which neighborhoods are perceived and influence substance use behaviors in Jamaica likely differ from that of more developed western countries, especially considering recent changes (2015) to the country’s national drug act which loosened restrictions on personal use of marijuana [61]. Furthermore, crime remains a main public safety issue for Jamaicans and a significant threat to the country’s human and economic development [64]. Jamaica has homicide rates that are notably higher than both the regional and global averages falling within the top 10% globally with increases since 2015 [65, 66].…”
Section: Introductionmentioning
confidence: 99%
“…[23, 27, 63] The way in which neighborhoods are perceived and influence substance use behaviors in Jamaica likely differ from that of more developed western countries, especially considering recent changes (2015) to the country’s national drug act which loosened restrictions on personal use of marijuana [61]. Furthermore, crime remains a main public safety issue for Jamaicans and a significant threat to the country’s human and economic development [64]. Jamaica has homicide rates that are notably higher than both the regional and global averages falling within the top 10% globally with increases since 2015 [65, 66].…”
Section: Introductionmentioning
confidence: 99%
“…A recent IDB Series on Crime and Violence in the Caribbean, a region-wide research project, found that while there are different levels of crime across the Caribbean, overall crime and violence have presented a significant hindrance to development and the social fabric of the region. Jamaica, for instance, is one of the most violent places in the world, with 'homicide rates that are notably higher than both the regional and global averages' [34] (p. ix). In Bahamas, the IDB report [35] finds that 'levels of crime and violence have consistently risen during the past decade .…”
Section: The Historical and Socio-economic Context Of The Caricommentioning
confidence: 99%
“…10 Seventy-one percent of rural parents and 55 percent of urban parents reported flogging as the most frequent response to perceived misbehaviour in their children. 11 Even though administrative data on assault and sexual violence are not comparable between countries, data on these crimes are available in several IDB publications (Bailey 2016;Harriott and Jones 2016;Seepersad 2016;Sutton 2016). 12 Accurately determining the cause of death is still a challenge in many countries that may have scarce time and resources to conduct crime scene investigations and autopsies.…”
Section: Intimate Partner and Family-related Homicidementioning
confidence: 99%